Analisis Partisipasi dan Motivasi Siswa dalam Program Senam Anak Indonesia Hebat - Saubari, Muhammad Rifqi; Jusuf, Jeane Betty Kurnia; Santoso, Januar Abdilah (Jurnal Muara Olahraga, 2025)
The Indonesian Children's Gymnastics Excellence Program (SAIH) is a national effort to get more elementary school pupils to be active. This cross-sectional study looked at how many students participated in the SAIH program and how motivated they were, as well as how these factors were related to their body mass index (BMI) and other demographic factors. In May 2025, fifty fifth-grade kids (average age 11.8 years) from SDN 007 Sungai Pinang took part. We used a validated motivation questionnaire (30 items, α=0.87) and anthropometric measurements to gather data. We used SPSS 26.0 to do descriptive statistics, correlation tests, and multiple regression. The results showed that motivation levels were high (M=121.8; SD=17.4), with a significant difference between males and females (p=0.032). Female students were more motivated (M=125.4) than male students (M=118.7). There was a strong negative relationship between BMI and motivation (r=-0.421; p<0.01). Students who were at a healthy weight were 23% more likely to participate than students who were overweight. There was a 28.9% difference in motivation that could be explained by the regression model, with gender and BMI being the most important factors. These results show that the SAIH program gets good feedback from students, but demographic characteristics and nutritional status have a big impact on how many students sign up and how motivated they are to participate. To get the most out of the curriculum for all pupils, it is suggested that more inclusive methods be used.